2019
DOI: 10.1002/ejoc.201901273
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Synthesis of Symmetrical and Unsymmetrical Ureas Using Chromium Hexacarbonyl as a Convenient and Safe Alternative Carbonyl Source

Abstract: Pd-catalyzed synthesis of urea derivatives from aryl iodides and different aliphatic and aromatic amines using sodium azide and chromium hexacarbonyl is described. In this process, carbonylation of aryl iodides, Curtius rearrangement of [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…1-(2-Methylphenyl)-3-(4-methylphenyl)urea ( 1ag ) [ 35 ]. Prepared from p -toluidine and o -methylphenyl isocyanate.…”
Section: Methodsmentioning
confidence: 99%
“…1-(2-Methylphenyl)-3-(4-methylphenyl)urea ( 1ag ) [ 35 ]. Prepared from p -toluidine and o -methylphenyl isocyanate.…”
Section: Methodsmentioning
confidence: 99%
“…The aforementioned importance of urea leads to substantial experimental research which has been done on the synthesis of symmetrical and unsymmetrical urea. A literature survey revealed that there are numerous advanced methods have been developed for the synthesis of urea molecules including triazene‐linked amine, [13] modified Curtius rearrangement with acid halide, [14] palladium with chromium carbonyl, [15] Staudinger‐aza‐Wittig reaction, [16] and tandem urea synthesis by using DPPA [17] (Scheme 1). In addition to these, there were several approaches had been developed with CDI by using methyl sulphonic acid, [18] triethyl amine, [19] and polymer‐linked amines [20] .…”
Section: Introductionmentioning
confidence: 99%
“…The first route includes reactions in which the carbonyl group is introduced from the outside. These are palladium‐catalyzed cross‐coupling of aryl chlorides and triflates with sodium cyanate, [48] catalytic reduction of nitro compounds at the presence of CO, [49] catalytic carbonylation of amines by carbon monoxide, [50–52] carbon dioxide, [53,54] and metal carbonyls [55] . As alternative to amines, the azides carbonylation protocol was developed by Zhang and co‐workers [56,57] .…”
Section: Introductionmentioning
confidence: 99%
“…These are palladium-catalyzed cross-coupling of aryl chlorides and triflates with sodium cyanate, [48] catalytic reduction of nitro compounds at the presence of CO, [49] catalytic carbonylation of amines by carbon monoxide, [50][51][52] carbon dioxide, [53,54] and metal carbonyls. [55] As alternative to amines, the azides carbonylation protocol was developed by Zhang and co-workers. [56,57] Latter this method has been recon-ceptualized in terms of the multicomponent chemistry.…”
Section: Introductionmentioning
confidence: 99%